A SPATIOSPATIOSPATIOSPATIOSPATIO -TEMPORALTEMPORALTEMPORALTEMPORAL TEMPORAL RETROSPECTIVE RETROSPECTIVE RETROSPECTIVE RETROSPECTIVE - R. A., Saouli1*, Benhassineenhassine N.; A., . Oularbi ularbi 3 (university of eloued جامعة الوادي, 2020)
Urban sprawl is a Urban sprawl is a Urban sprawl is a Urban sprawl is a Urban sprawl is a Urban sprawl is a Urban sprawl is a Urban sprawl is a Urban sprawl is a phenomenon phenomenon phenomenon with a negative effect which, over time, consumes the living a negative effect which, over time, consumes the living a negative effect which, over time, consumes the living a negative effect which, over time, consumes the living a negative effect which, over time, consumes the living a negative effect which, over time, consumes the living a negative effect which, over time, consumes the living a negative effect which, over time, consumes the living a negative effect which, over time, consumes the living a negative effect which, over time, consumes the living a negative effect which, over time, consumes the living a negative effect which, over time, consumes the living a negative effect which, over time, consumes the living a negative effect which, over time, consumes the living a negative effect which, over time, consumes the living a negative effect which, over time, consumes the living a negative effect which, over time, consumes the living a negative effect which, over time, consumes the living a negative effect which, over time, consumes the living a negative effect which, over time, consumes the living a negative effect which, over time, consumes the living a negative effect which, over time, consumes the living a negative effect which, over time, consumes the living a negative effect which, over time, consumes the living a negative effect which, over time, consumes the living environmentenvironment environment. The aim of this research is to The aim of this research is to The aim of this research is to The aim of this research is to The aim of this research is to The aim of this research is to The aim of this research is to The aim of this research is to The aim of this research is to The aim of this research is to The aim of this research is to The aim of this research is to The aim of this research is to The aim of this research is to The aim of this research is to analyze and analyze and analyze and analyze and analyze and analyze and evaluate evaluate evaluate evaluate evaluate the urban sprawl of Annaba urban sprawl of Annaba urban sprawl of Annaba urban sprawl of Annaba urban sprawl of Annaba urban sprawl of Annaba urban sprawl of Annaba situated at the northeast situated at the northeast situated at the northeast situated at the northeastsituated at the northeast situated at the northeast situated at the northeast situated at the northeastsituated at the northeast ernern part of Algeria part of Algeria part of Algeria part of Algeria part of Algeria part of Algeria in a diachronic approach. The studied area contains in a diachronic approach. The studied area contains in a diachronic approach. The studied area contains in a diachronic approach. The studied area contains in a diachronic approach. The studied area contains in a diachronic approach. The studied area contains in a diachronic approach. The studied area contains in a diachronic approach. The studied area contains in a diachronic approach. The studied area contains in a diachronic approach. The studied area contains in a diachronic approach. The studied area contains in a diachronic approach. The studied area contains in a diachronic approach. The studied area contains in a diachronic approach. The studied area contains in a diachronic approach. The studied area contains in a diachronic approach. The studied area contains in a diachronic approach. The studied area contains in a diachronic approach. The studied area contains in a diachronic approach. The studied area contains in a diachronic approach. The studied area contains in a diachronic approach. The studied area contains in a diachronic approach. The studied area contains in a diachronic approach. The studied area contains in a diachronic approach. The studied area contains twelve twelve agglomerations.agglomerations. agglomerations.agglomerations.agglomerations.agglomerations. agglomerations. Through the supervised classification of a time series data provided Through the supervised classification of a time series data provided Through the supervised classification of a time series data provided Through the supervised classification of a time series data provided Through the supervised classification of a time series data provided Through the supervised classification of a time series data provided Through the supervised classification of a time series data provided Through the supervised classification of a time series data provided Through the supervised classification of a time series data provided Through the supervised classification of a time series data provided Through the supervised classification of a time series data provided Through the supervised classification of a time series data provided Through the supervised classification of a time series data provided Through the supervised classification of a time series data provided Through the supervised classification of a time series data provided Through the supervised classification of a time series data provided Through the supervised classification of a time series data provided Through the supervised classification of a time series data provided Through the supervised classification of a time series data provided Through the supervised classification of a time series data provided Through the supervised classification of a time series data provided Through the supervised classification of a time series data provided Through the supervised classification of a time series data provided Through the supervised classification of a time series data provided Through the supervised classification of a time series data provided Through the supervised classification of a time series data provided Through the supervised classification of a time series data provided by multi spectral sensors mounted on LANDSAT 8 Operati by multi spectral sensors mounted on LANDSAT 8 Operati by multi spectral sensors mounted on LANDSAT 8 Operati by multi spectral sensors mounted on LANDSAT 8 Operatiby multi spectral sensors mounted on LANDSAT 8 Operati by multi spectral sensors mounted on LANDSAT 8 Operatiby multi spectral sensors mounted on LANDSAT 8 Operati by multi spectral sensors mounted on LANDSAT 8 Operati by multi spectral sensors mounted on LANDSAT 8 Operati by multi spectral sensors mounted on LANDSAT 8 Operati by multi spectral sensors mounted on LANDSAT 8 Operati by multi spectral sensors mounted on LANDSAT 8 Operatiby multi spectral sensors mounted on LANDSAT 8 Operati by multi spectral sensors mounted on LANDSAT 8 Operati by multi spectral sensors mounted on LANDSAT 8 Operati by multi spectral sensors mounted on LANDSAT 8 Operati by multi spectral sensors mounted on LANDSAT 8 Operatiby multi spectral sensors mounted on LANDSAT 8 Operatiby multi spectral sensors mounted on LANDSAT 8 Operatiby multi spectral sensors mounted on LANDSAT 8 Operatiby multi spectral sensors mounted on LANDSAT 8 Operati by multi spectral sensors mounted on LANDSAT 8 Operati by multi spectral sensors mounted on LANDSAT 8 Operati by multi spectral sensors mounted on LANDSAT 8 Operati onal Land Imager (OLI), onal Land Imager (OLI), onal Land Imager (OLI), onal Land Imager (OLI), onal Land Imager (OLI), onal Land Imager (OLI), onal Land Imager (OLI), onal Land Imager (OLI), onal Land Imager (OLI), onal Land Imager (OLI), onal Land Imager (OLI), onal Land Imager (OLI), onal Land Imager (OLI), LANDSAT LANDSAT LANDSATLANDSATLANDSAT 7 T hemhemhematic Mapperatic Mapper atic Mapperatic Mapperatic Mapper atic Mapper atic Mapper Plus satellite platformsPlus satellite platforms Plus satellite platformsPlus satellite platforms Plus satellite platforms Plus satellite platformsPlus satellite platforms Plus satellite platforms (ETM (ETM +) and L+) and L +) and L +) and L ANDSAT 4 ANDSAT 4 ANDSAT 4ANDSAT 4 -5 Thematic 5 Thematic 5 Thematic 5 Thematic Mapper (TM) Mapper (TM) Mapper (TM) Mapper (TM) Mapper (TM)Mapper (TM), the urban he urban he urban he urban he urban sprawl sprawl was examined was examined was examined was examined was examined was examined was examined was examined in different periods of 1987, 2013 and 2017 n different periods of 1987, 2013 and 2017 n different periods of 1987, 2013 and 2017 n different periods of 1987, 2013 and 2017n different periods of 1987, 2013 and 2017n different periods of 1987, 2013 and 2017 n different periods of 1987, 2013 and 2017 n different periods of 1987, 2013 and 2017 n different periods of 1987, 2013 and 2017 n different periods of 1987, 2013 and 2017 n different periods of 1987, 2013 and 2017 n different periods of 1987, 2013 and 2017 n different periods of 1987, 2013 and 2017n different periods of 1987, 2013 and 2017 n different periods of 1987, 2013 and 2017 , on defferent on defferent on defferent on defferent on defferent on defferent on defferent scalescalescales . This study This study This study displayed that displayed thatdisplayed that displayed that displayed that a
artical
Keywords: ban sprawl, GIS, remote sensing, diachronic approach, Annaba urban sprawl, GIS, remote sensing, diachronic approach, Annaba urban sprawl, GIS, remote sensing, diachronic approach, Annaba urban sprawl, GIS, remote sensing, diachronic approach, Annaba urban sprawl, GIS, remote sensing, diachronic approach, Annaba urban sprawl, GIS, remote sensing, diachronic approach, Annabaurban sprawl, GIS, remote sensing, diachronic approach, Annabaurban sprawl, GIS, remote sensing, diachronic approach, Annaba urban sprawl, GIS, remote sensing, diachronic approach, Annaba urban sprawl, GIS, remote sensing, diachronic approach, Annabaurban sprawl, GIS, remote sensing, diachronic approach, Annaba urban sprawl, GIS, remote sensing, diachronic approach, Annaba urban sprawl, GIS, remote sensing, diachronic approach, Annaba urban sprawl, GIS, remote sensing, diachronic approach, Annabaurban sprawl, GIS, remote sensing, diachronic approach, Annabaurban sprawl, GIS, remote sensing, diachronic approach, Annaba urban sprawl, GIS, remote sensing, diachronic approach, Annabaurban sprawl, GIS, remote sensing, diachronic approach, Annabaurban sprawl, GIS, remote sensing, diachronic approach, Annaba urban sprawl, GIS, remote sensing, diachronic approach, Annabaurban sprawl, GIS, remote sensing, diachronic approach, Annaba urban sprawl, GIS, remote sensing, diachronic approach, Annaba